Fixation of A Closed Displaced Midshaft Clavicle Fracture by Intramedullary K-Wire: A Case Report - Devuandre Naziat; David Haryadi (Universitas Airlangga, 2021)
Background: Fractures of the clavicle record for practically 50% of all injuries in the shoulder girdle. In recent years, the treatment paradigm for clavicle fractures has shifted from nonoperative treatment toward operative treatment, especially in fractures with significant displacement or shortening. Case Report: A 16 years old female presented to the emergency room with an injury on her right shoulder after a motorcycle accident. The radiograph showed a displaced midshaft clavicle fracture, classified as Robinson 2B1.Â Operative measures were performed using intramedullary K-Wire. Discussion: There is no universally agreed gold standard for clavicle fracture fixation. The majority of midshaft clavicle fractures with a displaced fragment can be successfully repaired without surgery. On the other hand, conservative therapy of Robinson type 2B clavicle fracture has been linked to a higher rate of nonunion and a decrease in strength and endurance of the shoulder. In this patient, on the two-week follow-up after wire removal surgery, the patient regained full shoulder range of motion without any limitation on activities of daily living with a minimal post-operative scar.Conclusion: We recommend that intramedullary fixation using K-wires is a useful technique in displaced midshaft clavicle fracture as it is effective, has a good cosmetic outcome, and is well-suited for the BPJS era as it had the low-cost burden.